Perceptions of MSME Actors Towards Using QRIS as a Cash Transaction Tool in Area Universitas Muhammadiyah Surakarta - Putra, Kristyawan Wihayanto; Wahyudi, Tri Nur (Yayasan Sinergi Kawula Muda, 2025)
This study aims to examine the perceptions of MSME actors regarding the use of QRIS as a non-cash transaction tool in the area of Muhammadiyah University of Surakarta, where the variables of perceived ease of use, perceived benefits, perceived risks, and perceived security represent perceptions. This type of research is quantitative, and the data used is primary. The data collection process in this study was conducted by distributing a questionnaire to respondents using Google Forms. Data analysis techniques with research instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. Data processing using the SPSS program. The research results indicate that the perception of ease of use significantly affects the use of QRIS among MSME actors in the area of Universitas Muhammadiyah Surakarta, the perception of benefits substantially affects the use of QRIS among MSME actors in the area of Universitas Muhammadiyah Surakarta, the perception of risk does not significantly affect the use of QRIS among MSME actors in the area of Universitas Muhammadiyah Surakarta, and the perception of security does not significantly affect the use of QRIS among MSME actors in the area of Universitas Muhammadiyah Surakarta.